A Single Layer of Chromium Oxide Nanoparticles Films Coated with Carbon by Applying Exploding Wire Technique for Efficient Solar Selective Absorber - Abdullah, Sawsan H.; Humud, Hammad R.; Mustafa, Falah. I. (Iraqi Journal of Science, 2022)
The efficiency of solar energy absorption in solar heaters is increased by the use of selective absorption coating that possesses high absorption of solar radiation in the UV-visible spectrum as well as low emission at the operating temperature in the infrared region. In this work, novel selective coatings were synthesized by improving the selectivity of chromium oxide (Cr2O3) nanoparticles by doping with carbon nanoparticles using the exploding wire technique for carbon rods by high current in suspended Cr2O3 particles. The structural properties and surface topography were studied by XRD and FE-SEM, which illustrate the carbon-coated Cr2O3 nanoparticles. The prepared nanoparticles were mixed with a support material, Polyvinyl pyrrolidone (PVP) as a matrix, for use as a selective coating for three metals, namely copper, aluminium and stainless steel (SST). Reflectivity measurements were performed within the UV-Visible spectrum to calculate the absorption of solar radiation using numerical integration. The reflectivity was also measured in the range from 2.5 to 25 μm to calculate the thermal emission of the solar heater within the proposed operating temperature of 373 K. The measurements showed good efficiency of using the produced material as a selective coating which was prepared in a simple way compared to conventional methods. The best sample with efficient absorptance (α) for solar spectrum and of lowest emittance (ε) in IR region was for Al substrate coated by Cr2O3:C:PVP of α =0.886 and ε= 0.260.